Covid-19 effect on community mobility and stock market of Malaysia - Norhafizah Abu Hasan,; Wee, Hin Boo; Wong, Wai Yan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Physical distancing is believed to contain the spread of COVID-19 virus. With data provided by COVID-19 Community Mobility Reports from Google, this study examines the mobility patterns at different stages of Movement Control Order (MCO) and investigates whether lower mobility reduces the number of new cases, death cases, and recovery rate. This research also covers the time spent in places such as i) retail and recreation, ii) grocery and pharmacy, iii) parks, iv) transit stations, v) the workplace, and vi) residential areas. As each of these types of places has distinct epidemiological characteristics, they may spread transmission differently. This study also correlates the stock market with mobility patterns of Malaysians in order to evaluate the effectiveness of lockdowns on COVID-19 incidents and its impact on the stock market, in this case; Kuala Lumpur Composite Index (KLCI). Findings of this study highlight the effects of pandemic COVID-19 on stock market daily performance by utilizing prospect and uncertainty theory in predicting the short-term impacts of the epidemic.